The better route to global tax coordination: Gradualism or multilateralism? - Kai A. Konrad; Marcel Thum (Canadian Journal of Economics/Revue canadienne d'économique, 2021)
We compare the success probability of multilateral negotiations and sequential negotiations over international tax cooperation. To make this difference relevant, we introduce incomplete information as a friction that can lead to bargaining failure. We find plausible conditions for when multilateral negotiations are more likely to achieve full global tax coordination than a gradual/sequential approach. We also compare different routes of sequential bargaining. We ask whether negotiations should start with countries that are the most unpredictable candidates or the most difficult negotiation should be preserved for the final round. We find that sequencing along this dimension matters. Under plausible conditions, full cooperation is least likely to emerge if the negotiations with the most unpredictable country take place last.
Keywords: 330